A Comparative study between the prevalence of MTHFR A1298C SNP and homocysteine metabolism in an elderly black South African population - Dippenaar, Luzanne (Vaal University of Technology, 2018)
Background: Cardiovascular diseases are one of the most common causes of death worldwide. This is not only a problem in developed countries, it is of major concern for public health in developing countries as well. Increased homocysteine is an independent risk factor for cardiovascular diseases. Nutritional deficiencies of folate, vitamin B6 and vitamin B12 are associated with hyperhomocysteinemia. MTHFR A1298C, a single nucleotide polymorphism, is similarly linked with higher concentrations of homocysteine. The aim of this study was to determine the prevalence of MTHFR A1298C in a black elderly population, along with folate, vitamin B6 and vitamin B12 and to evaluate the effect on homocysteine levels. Methodology: The research design was an observational cross-sectional study and was ethically approved. A total of 84 elderly who attend a day-care centre (also met inclusion criteria) were purposively selected. DNA was extracted and frozen on the day of blood collection. The MTHFR A1298C genotype was determined with real time PCR. Homocysteine, folate, vitamin B6 and vitamin B12 serum levels were detected with commercial assay kits. Results: Homocysteine was found to be elevated with a median of 17.78 µmol/L (interquartile range 13.98-21.03 µmol/L). Serum folate, vitamin B6 and vitamin B12 medians were in the normal range. Although, 5.95% and 22.62% of the population were deficient and possibly deficient for vitamin B12, respectively. MTHFR A1298C frequency was as follow: 89.29% (AA), 9.52% (AC) and 1.19% (CC), with no significant correlation (p>0.05) with homocysteine. Vitamin B12 correlated significantly with homocysteine levels. Conclusion: Vitamin B12 deficiency had an effect on homocysteine levels. Overall, nutritional deficiencies are not responsible for the hyperhomocysteinemia in this population. In conclusion from this study showed MTHFR A1298C frequency in black South Africans does not contribute to homocysteine as a risk factor for cardiovascular disease. Keywords: Cardiovascular disease, elderly, folate, homocysteine, MTHFR A1298C, vitamin B6, vitamin B12.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Cardiovascular diseases; MTHFR A1298C; Nucleotide polymorphism; Homocysteine -- Pathophysiology.; Homocysteine -- Metabolism -- Disorders.; Older people -- Diseases -- Treatment.; Cardiovascular system -- Diseases -- Treatment.; Dissertations, Academic -- South Africa.